2006
DOI: 10.1016/j.jmaa.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of predator–prey systems described by a Lotka–Volterra equation under random environment

Abstract: In this paper, we consider the evolution of a system composed of two predator-prey deterministic systems described by Lotka-Volterra equations in random environment. It is proved that under the influence of telegraph noise, all positive trajectories of such a system always go out from any compact set of int R 2 + with probability one if two rest points of the two systems do not coincide. In case where they have the rest point in common, the trajectory either leaves from any compact set of int R 2 + or converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(91 citation statements)
references
References 13 publications
(19 reference statements)
2
89
0
Order By: Relevance
“…However, this is not the only way to introduce stochasticity into the deterministic model (2). There is another type of environmental noise, namely color noise, say telegraph noise [14][15][16][17][18]. Telegraph noise can be illustrated as a switching between two or more regimes of environment, which differ by factors such as nutrition, climatic characteristics or socio-cultural factorsfactors.…”
Section: S(t) = μ − μS(t) − β S(t)i (T) + γ R(t) Dt D I (T) = [−(μ +mentioning
confidence: 99%
“…However, this is not the only way to introduce stochasticity into the deterministic model (2). There is another type of environmental noise, namely color noise, say telegraph noise [14][15][16][17][18]. Telegraph noise can be illustrated as a switching between two or more regimes of environment, which differ by factors such as nutrition, climatic characteristics or socio-cultural factorsfactors.…”
Section: S(t) = μ − μS(t) − β S(t)i (T) + γ R(t) Dt D I (T) = [−(μ +mentioning
confidence: 99%
“…The Markov chain has important impacts on the population dynamics. Takeuchi et al [34] revealed the significant effect of Markovian switching on the population system: both its subsystems develop periodically but switching between them makes them become neither permanent nor dissipative. Let us take a more further step, in reality, due to some natural or man-made factors, the growth of species often undergoes some discrete changes of relatively short time interval at some fixed times, such as drought, flooding, hunting, planting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many authors introduced stochastic perturbations into the deterministic models [16,19,29,33]. Takeuchi et al [28] considered the following predator-prey model with telegraph noise based on model (1.1):…”
Section: Introductionmentioning
confidence: 99%
“…In fact, two equilibrium states often do not coincide with each other. Takeuchi et al [28] discovered that the stochastic species system is neither permanent nor dissipative (see, e.g., [5]). This is an important result as it reveals a significant effect on the species system, i.e., both its subsystems evolved periodically, but the switching made them neither permanent nor dissipative.…”
Section: Introductionmentioning
confidence: 99%